How might we motivate uptake of the Dual Prevention Pill? Findings from human-centered design research with potential end users, male partners, and healthcare providers - Nyagah, Wawira; Segal, Kate; Feltham, Jess; Ash, Alex; Major, Jocelyn; Masani, Moowa (Frontiers in Reproductive Health, 2023)
Introduction Multipurpose prevention technologies (MPTs) combining contraception with HIV prevention offer a promising solution to uptake and adherence challenges faced with oral pre-exposure prophylaxis (PrEP). The Dual Prevention Pill (DPP), which combines oral PrEP with an oral contraceptive pill (OCP), could address unmet need for family planning (FP) and HIV prevention. This study aimed to identify barriers and motivators for DPP uptake to inform the development of a DPP demand generation strategy and broader introduction efforts for MPTs. Materials and methods Qualitative, ethnographic research employing human-centered design techniques was conducted in Kenya, South Africa, and Zimbabwe. A research consortium conducted 45 immersions, 34 key informant interviews, and 12 friendship circles with potential end users, male romantic partners, healthcare providers (HCPs), and cultural commentators. Creative concepts were subsequently co-created and validated in workshops with end users, male partners, and HCPs. Results Four major themes emerged. Women struggled to balance personal motivations with societal expectations. Relationship goals strongly influenced sexual and reproductive health decisions, particularly related to financial security and social status. Negative experiences, such as untrustworthy partners, were significant triggers for OCP and PrEP use. Lastly, male partners were concerned about the DPP upending gender norms but held more positive individual attitudes. Five initial audience segments for the DPP were identified: women seeking enjoyment outside of their primary relationship; new mothers adhering to social norms; women wanting to maintain romantic relationships; women at risk of unintended pregnancy; and women with unfaithful partners. Segments informed the development of three communication themes, with the preferred route highlighting the DPP as a tool to prepare for life's unpredictability. Discussion To effectively generate demand for the DPP, several strategies should be considered. Connecting with women's diverse identities and goals and celebrating their individuality is crucial. Linking the DPP to relationship goals reframes it as a means to protect relationships rather than a risk. Leveraging negative triggers through targeted media campaigns empowers women to take control of their sexual health during challenging moments. A balance in channel placement is necessary to raise public awareness while using more discrete channels for potentially controversial messages with male partners and wider communities.